352 Feeding treated wheat straw to weaned pigs improves feed efficiency and impacts mucosal and system immune parameters. (5th December 2019) - Lewton, Jaron R; Michael, Medhat A; Rajput, Mrigendra; Thelen, Kyan M; Moeser, Adam J; Rozeboom, Dale W
Abstract: A management challenge on swine farms is the successful weaning of piglets. Recently, the management of weaning has become more challenging with society's goal to diminish antimicrobial use. Dietary fiber is increasingly thought important for improving the gastrointestinal development and function, health and the growth performance of the young animal. The objective was to evaluate the effects of feeding treated wheat straw (TWC, with acid, heat, and calcium carbonate) to weaned pigs. At 27.1 ± 1.3 d of age, 108 crossbred (PIC 327 x Yorkshire) pigs were weaned and randomly allotted to 3 treatments: 1) control, 2) 5% TWS, and 3) 10% TWS. Treatments were imposed over 3 nursery phases (7, 7 and 14 d, respectively). All diets met or exceed the nutrient requirements of NRC (2012) and were isocaloric within each phase. No antibiotic was fed, and neither were pharmacological amounts of copper or zinc. There were 6 pens (6 pigs per pen) per treatment. Pig gains were maintained, and feed efficiency improved with TWS in the diet (Table 1). Relative to controls, inclusion of TWS tended to increase (P = 0.12) major histocompatibility complex (MHC) class II expression in peripheral blood circulating monocytes (PBMC), an index of enhanced antigen presentation to the immune system, which may reflect an enhanced development of immune function. A trend (P = 0.10) for lower serum IgA levels (marker of mucosal immunity) was observed in pigs fed 10% TWS, compared with other treatments. Overall these data suggest that dietary TWS benefited growth performance and influenced mucosal and systemic immune measures which may provide benefits to health.